PENATALAKSANAAN FISIOTERAPI PADA KONDISI OSTEOARTHRITIS KNEE DEKSTRA DENGAN MODALITAS ULTRASOUND DAN TERAPI LATIHAN DI RSUD Prof. Dr. MARGONO SOEKARJO - Merri Yusdiana; Eko Budi Prasetyo (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
Osteoarthritis  is  a  common  rheumatic  disease  and  causes  pain  and  inability  to perform  daily  activities.  Osteoarthritis  is  caused  by  several  factors  such  as:  age, obesity,  physical  activity,  sex,  hormonal,  and  idiopathic  causes  damage  to  the cartilage resulting in reduced mobility, pain and decreased muscle strength. Handlers in  this  state  first  examined  pain  with  VDS  scale,  examination  of  muscle  strength (MMT), examination of range of motion and functional activity. The modalities used in  this  condition  is  Ultra  Sound  (US)  and  exercise  therapy. From  the  results  obtained,  it  can  be  concluded  that  the  use  of  ultrasound  modalities and  therapeutic  exercises  can  help  reduce  the  problems  that  arise  in  the  case  of osteoarthritis.Key  words:  Osteoarthritis  with  VDS, MMT,  LGS,  ADL  Index,  ultrasound  and exercise therapy.